Counselor viewpoints on the formation of theoretical orientation - Weber, Brian W. (Kansas State University, 2020)
A key task in the professional development of counselors is the formation and refinement of their theoretical orientation, a framework based in theories of counseling and psychotherapy which helps one to understand human behavior and guide the therapeutic process. This study sought to explore counselor viewpoints on the current stage of their theoretical orientation formation, find common viewpoints among counselors about this process, and understand if there are any demographic similarities among counselors with a similar viewpoint. To examine if there were any commonalities in viewpoint between counselors of similar specialties, practicing counselors and counseling students from the school counseling and clinical mental health counseling specialties were recruited. In addition, to examine if there were any commonalities based on level of experience in the counseling profession, participants were recruited from five experience levels: the first half of one’s graduate program, the second half of one’s graduate program, early in one’s career as a practicing counselor (years 1-5), the middle of one’s career (years 6-15), and an advanced stage in one’s career (over 15 years). To understand this process, this study utilized Q methodology, a hybrid quantitative and qualitative approach which explores human subjectivity (Brown, 2012; Newman & Ramlo, 2017; Watts & Stenner, 2012). In this methodology, participants are shown a series of statements, in this case 54 statements derived from previous research describing various elements which can influence the formation of one’s theoretical orientation. In this study, 32 practicing counselors and counseling students were asked to sort these statements based on their agreement or disagreement with each statement onto a forced-choice distribution grid. Then, the overall sorting pattern of these statements was analyzed using an inverse factor analysis process unique to Q methodology studies which showed correlations between the viewpoints of all of the participants and helped to determine common viewpoints, referred to as typologies in Q methodology studies, among the participants. Five distinct typologies were identified. Typology 1 included participants who demonstrated confidence in one’s practices and a preference for a core theory upon which one could integrate a variety of techniques. In Typology 2, participants demonstrated a struggle to balance one’s desire for finding a theory to express oneself with a feeling that one should be prepared with the perfect theory for every situation. Participants in Typology 3 focused on the value of well-established theories based in scientific principles. Those in Typology 4 valued using a variety of theories and learning through social interaction. Finally, participants in Typology 5 indicated a need for growth through education and experience. No statistically significant connections were found between any of the typologies and the demographics of counseling specialty area or experience level, but some observable patterns are detailed. Implications for the counseling profession and counseling education are discussed and recommendations are made for future studies.
Keywords: Counseling; Counselor Education; Theoretical Orientation; Q methodology